THE IMPLEMENTATION OF TEACHING GENRE IN L2 LISTENING CLASSROOM: IRANIAN PRE-INTERMEDIATE EFL LEARNERS IN FOCUS - Ehsan Namaziandost; Sajad Shafiee; Behrouz Ahmadi (University of Kuningan, 2019)
This study tries to implement genre-based instruction in Iranian pre-intermediate EFL learners’ L2 listening skill. Moreover, it aims to investigate if genre-based instruction impacts the listening skills of EFL learners at different skill levels equally. To achieve this goal, 60 EFL learners have been selected. These were split into groups A and B. Groups A and B, respectively, consisted of 30 and 30 members. Group A was split into experimental and control groups and administered the pre and posttest of listening skills. Findings from one-way ANCOVA showed that because of using genre-based instruction, the experimental group outperformed the control group. Group B was also classified into proficient and less-proficient classes as demonstrated by the proficiency test; each administered two pre-and posttest of listening. Nonetheless, the findings of one-way ANCOVA revealed that both classes were improved from pretest to posttest; the professional group performed remarkably better than the less skilled group. Generally speaking, the results of this study showed that GBT is a key and crucial factor in developing listening comprehension.